Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Konsumen Produk Perawatan Kulit Merek Skintific di Jakarta Barat - Wati, Tri Mulya; Ruminta, Darkiman; Akbar, Dudi Duta (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research has a background problem that is the promotion and price of Skintific brand products to consumers in West Jakarta. This skincare trend is increasing along with modern lifestyles and the influence of social media. Skintific has become a popular brand due to its aggressive marketing strategy, especially on TikTok. Although known as a premium quality product, Skintific's price is considered not commensurate with its quality when compared to local brands. The "FOMO" phenomenon makes many consumers buy because of trends, not needs. This shows that purchasing decisions are influenced by brand image and promotion, not just product quality. The sampling technique used is non-probability sampling with a purposive method, a sample size of 96 respondents. Data analysis used SPSS version 25. Researchers conducted several tests including multiple linear analysis, classical assumption tests, hypothesis tests and coefficient of determination tests. The results of the T test showed that promotion and price had a significant effect on purchasing decisions with a significance value of 0.000 <0.05 and the results of the F test showed that promotion and price had a simultaneous effect on purchasing decisions because the F count value of 48.884> f table 3.09